Al-Anāşir al-Adabiyah fῑ al-Qişşah al-Qaşῑrah “Wa Kānat al-Dunya” lῑ Taufῑq al-Hākim: Dirāsah al-Nażariyah al-Bunyawiyah lῑ Aḥmad Al-Syā’ib - Rania Khoiru Nisa; Abdul Latif (JICALLS: Journal of Arabic Education, Linguistics, and Literature Studies, 2023)
This study aims to determine the intrinsic elements such as Aṭifah, Khayāl, Fikrah, and Şūrah using Ahmad al- Al-Syā’ib 's structuralism theory in the short story Wa Kānat al-Dunya by Taufik Al-Hakim. The type of research used is a qualitative approach. The qualitative type used is descriptive qualitative with data collection methods, namely research through short story texts. The data sources in this study are primary and secondary data sources such as analyzing the data obtained, namely short stories, discussing the problems obtained in the short stories and applying them to the problems to be discussed. Drawing conclusions from the results of the study, the results obtained are that Aṭifah has five parts, namely suduq al-aṭifah ’emotional authenticity’, quwwatu al-aṭifah ‘emotional strength’, sabat al-aṭifah ‘emotional toughness’, tanawwu’u al-aṭifah ‘emotional diversity’ and sumuw al-aṭifah ‘emotional level’. Khayāl, has three parts namely Ibtikāri ’Innovative’, Ta'lifi ’compositional’, and Bayāni ’graphic’. Fikrah type Sihah Al-Afkār ‘correct thinking’ and Şūrah there are three parts namely al-wuduh ’ clarity’, al-quwwah ‘strength’, and al-jamal ‘beauty’.